Comparison of the modified Smith-Petersen (S-P) and ilioinguinal (I-I) approaches for periacetabular osteotomy in adult developmental dysplasia of the hip: a retrospective study - Rui Luo; Guomin Li; Bo Li; Ruyin Hu; Yankun Li (Journal of Orthopaedic Surgery and Research, 2021)
Abstract Background Adult developmental dysplasia of the hip is an untreated congenital hip dysplasia that results in adult hip pain. One of the usual and effective methods for the treatment of this condition is periacetabular osteotomy. However, which approach is better between the modified S-P and the I-I approaches is still unclear and controversial. Method and materials We retrospectively assessed our experience with the modified S-P and the I-I approaches by inquiring and evaluating intraoperative blood loss, postoperative radiographic material, postoperative function of the hip, and related complications from July 2014 to January 2019. Results A total of 61 patients with adult developmental dysplasia of the hip were enrolled, and 33 patients were divided into a modified S-P group and 28 patients were divided into I-I group. The operation time and blood loss of group I-I were higher than that of group modified S-P. Other clinical and radiographic indexes showed no statistical significance between group the modified S-P and I-I groups. Conclusion There is no significant difference in the improvement of the function of the hip at the post-operation stage, but group I-I may require more operation time and blood loss at the intra-operation stage.